2017
DOI: 10.1155/2017/7612748
|View full text |Cite
|
Sign up to set email alerts
|

QT Prolongation due to Graves’ Disease

Abstract: Hyperthyroidism is a highly prevalent disease affecting over 4 million people in the US. The disease is associated with many cardiac complications including atrial fibrillation and also less commonly with ventricular tachycardia and fibrillation. Many cardiac pathologies have been extensively studied; however, the relationship between hyperthyroidism and rate of ventricular repolarization manifesting as a prolonged QTc interval is not well known. Prolonged QTc interval regardless of thyroid status is a risk fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 6 publications
1
9
2
Order By: Relevance
“…Numerous studies have shown a strong association between hyperthyroidism and QTc prolongation. A positive correlation between free T4 and the degree of QT prolongation was seen; patients with higher levels of free T4 had longer QTc duration [1,[3][4][5][6][7][8]. This positive correlation was present with our patient: as free T4 increased, QTc also increased ( Table 1).…”
Section: Discussionsupporting
confidence: 69%
See 4 more Smart Citations
“…Numerous studies have shown a strong association between hyperthyroidism and QTc prolongation. A positive correlation between free T4 and the degree of QT prolongation was seen; patients with higher levels of free T4 had longer QTc duration [1,[3][4][5][6][7][8]. This positive correlation was present with our patient: as free T4 increased, QTc also increased ( Table 1).…”
Section: Discussionsupporting
confidence: 69%
“…This positive correlation was present with our patient: as free T4 increased, QTc also increased (Table 1 ). Normalization of free T4 leads and achievement of the euthyroid state has been shown to normalize QTc duration in hyperthyroid patients [ 4 ]. Although repeat-free T4 was not done in our patient after high dose methimazole treatment, serial QTc did show significant and continued improvement (Figure 1 and Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations